Screening mammography use in older women according to health status: a systematic review and meta-analysis - Demb J (Dove Medical Press, 2018)
Joshua Demb,1,2 Tomi Akinyemiju,3 Isabel Allen,1 Tracy Onega,4 Robert A Hiatt,1 Dejana Braithwaite2 1Department of Epidemiology and Biostatistics, University of California, San Francisco, CA, USA; 2Department of Oncology, Georgetown University School of Medicine, Washington, DC, USA; 3Department of Epidemiology, University of Kentucky, Lexington, KY, USA; 4Department of Biomedical Data Science, Geisel School of Medicine at Dartmouth, Hanover, NH, USA Background: The extent to which screening mammography (SM) recommendations in older women incorporate life expectancy factors is not well established. Objective: The objective of this review was to evaluate evidence on SM utilization in older women by life expectancy factors. Data sources: We searched Medline, Embase and Web of Science from January 1991 to March 2016. Study selection: We included studies examining SM utilization in women ages ≥65 years that measured life expectancy using comorbidity, functional limitations or health or prognostic status. Data extraction and synthesis: ORs and 95% CIs were extracted and grouped by life expectancy category. Findings were aggregated into pooled ORs and 95% CIs and meta-analyzed by life expectancy category. Main outcomes and measures: The primary outcome was SM utilization within the last 5 years. Life expectancy factors included number of comorbidities, Charlson Comorbidity Index (CCI), activities of daily living, instrumental activities of daily living, self-reported health status and 5-year prognostic indices. Results: Of 2,606 potential titles, we identified 25 meeting the inclusion criteria (comorbidity: eight studies, functional status: 11 studies and health/prognostic status: 13 studies). Women with higher CCI scores had decreased SM utilization (pooled OR: 0.75, 95% CI: 0.67–0.85), but increased absolute number of comorbidities were weakly associated with increased SM utilization (pooled OR: 1.17, 95% CI: 1.00–1.36). Women with more functional limitations had lower SM use odds than women with no limitations (pooled OR: 0.72, 95% CI: 0.62–0.83). Screening utilization odds were lower among women with poor vs excellent health (pooled OR: 0.85, 95% CI: 0.74–0.96). Conclusion: Greater CCI score, functional limitations and lower perceived health were associated with decreased SM use, whereas higher absolute number of comorbidities was associated with increased SM use. SM guidelines should consider these factors to improve assessments of potential benefits and harms in older women. Keywords: screening mammography, comorbidity, functional limitations, health status, meta-analysis